RELATIONSHIP QUALITY AMONG SPOUSES AND EX-SPOUSES OF VETERANS WITH DEMENTIA AS CAREGIVING CONTEXT. (11th November 2018) - Hilgeman, M; Block, P; Alexander, K; Collins, A; Kunik, M; Allen, R; Snow, A
Abstract: Factors that place military veterans at increased risk for dementia – such as post-traumatic stress disorder, depressive symptoms, or substance use – may also increase their risk of divorce or marital distress further complicating the caregiving context. The current paper examines known correlates and novel indicators of relationship quality to better understand marital satisfaction/distress in 27 married or divorced spousal caregivers and 18 community-dwelling veterans with dementia who completed a baseline assessment as part of an ongoing pilot study. Individuals with dementia (IWD) were 72.5 years and scored M = 16.8 (SD = 5.9) on the MOCA; caregivers were M = 69.8 years old, and had been married for M = 44 years (SD = 15.1). Caregiver scores on domains of the Dyadic Adjustment Scale (dyadic consensus, affectional expression, dyadic satisfaction, and dyadic cohesion) were highly correlated ranging from .525 to .912 (ps <.01), and total scores were significantly correlated with quality of life (.429, p = .029) and the IWD's depressive symptoms (-.478, p = .013). For IWD's, the mutuality scale was significantly related to their perceived dyadic satisfaction (.637, p = .003) and had a higher concordance with their caregivers ratings of mutuality (.463, p = .046); whereas ratings of marital or dyadic satisfaction between spouses had no association (.002, p = .994). Family relationship quality – and relationship type – are known to impact outcomes, such as frequency of challenging or responsive behaviors, for individuals with dementia. Understanding these factors is necessary to inform dyadic intervention approaches.